Workplace-based learning about health promotion in individual patient care: a scoping review - Willem J J Assendelft; Anneke M Landstra; Myrthe J M Verhees; Rik Engbers; Anne E Bremer; Marjolein van de Pol; Roland F J M Laan (BMJ Open, 2023)
Objective To outline current knowledge regarding workplace-based learning about health promotion in individual patient care.Design Scoping review.Data sources PubMed, ERIC, CINAHL and Web of Science from January 2000 to August 2023.Eligibility criteria We included articles about learning (activities) for healthcare professionals (in training), about health promotion in individual patient care and in the context of workplace-based learning.Data extraction and synthesis The studies were evaluated using a charting template and were analysed thematically using a template based on Designable Elements of Learning Environments model.Results From 7159 studies, we included 31 that described evaluations of workplace-based learning about health promotion, around a variety of health promotion topics, for different health professions. In the articles, health promotion was operationalised as knowledge, skills or attitudes related to specific lifestyle factors or more broadly, with concepts such as health literacy, advocacy and social determinants of health. We assembled an overview of spatial and instrumental, social, epistemic and temporal elements of learning environments in which health promotion is learnt.Conclusions The studies included in our analysis varied greatly in their approach to health promotion topics and the evaluation of learning outcomes. Our findings suggest the importance of providing opportunities for health profession learners to engage in authentic practice situations and address potential challenges they may experience translating related theory into practice. Additionally, our results highlight the need for conscious and articulated integration of health promotion in curricula and assessment structures. We recommend the exploration of opportunities for health profession students, professionals and patients to learn about health promotion together. Additionally, we see potential in using participatory research methods to study future health promotion learning.Study registration Open Science Framework, https://doi.org/10.17605/OSF.IO/6QPTV.